Contribution of cyclooxygenase-2 overexpression to enhancement in tonically active glutamatergic inputs to the rostral ventrolateral medulla in hypertension. Issue 12 (27th December 2022) - Fan, Jie-Fu; Wang, Wen; Tan, Xing; Ye, Peng; Li, Ji-Kui; Niu, Lu-Yu; Li, Wan-Yang; Wang, Wei-Zhong; Wang, Yang-Kai
Abstract : Objective: Cyclooxygenase (COX) is critical in regulating cardiovascular function, but its role involved in the central control of blood pressure (BP) is uncovered. The tonic glutamatergic inputs to the rostral ventrolateral medulla (RVLM) are enhanced in hypertension. Here, the present study was designed to investigate the effect and mechanism of central COX on tonic glutamatergic inputs to the RVLM and BP regulation. Methods: Wistar-Kyoto (WKY) rats and spontaneous hypertensive rats (SHRs) received RVLM microinjection of adeno-associated viral vectors to promote or inhibit the COX2 expression were subjected to subsequent experiments. Glutamate level and glutaminase expression were detected by ELISA and western blot, respectively. The function of tonic glutamatergic inputs was assessed by BP response to microinjection of the glutamate receptor antagonist into the RVLM. PC12 cells were used to detect the underlying signal pathway. Results: The RVLM COX2 expression and prostaglandin E2 level were significant higher in SHRs than in WKY rats. Overexpression of COX2 in the RVLM produced an increase in basal BP, RVLM glutamate level, and glutaminase expression in WKY rats, while they were significantly reduced by interfering with COX2 expression in SHRs. Microinjections of the glutamate receptor antagonist into the RVLM produced a significant BP decrease in WKY rats with COX2 overexpression pretreatment. Furthermore, the increased levels of BP, glutamate content, and glutaminase activity in the RVLM evoked by central infusion of angiotensin II were attenuated in COX2 knockout mice. It was also found that prostaglandin E2 increased supernatant glutamate level and phosphorylation of signal transducer and activator of transcription 3 in PC12 cells. Conclusion: Our findings suggest that upregulated COX2 expression enhances the tonically active glutamatergic inputs to the RVLM, which is associated with cardiovascular regulation in hypertension.